PENGGUNAAN MODEL BERBAGI PENGALAMAN TERHADAP HASIL BELAJAR IPA MELALUI PEMANFAATAN MEDIA KOMIK - Mutia, Wahyu; Maryadi, Maryadi; Subekti, Ervina Eka (Universitas Negeri Semarang, 2017)
Abstract. This study aims to find out how effective is using sharing experience model with comic media on the results of science learning of grade V students at SDN 1 Geneng District Jepon Blora regency for academic year 2016/2017. The form of this research is quantitative research with One Group Pretest-Posttest Design. This study was conducted during two meetings, where each meeting was held for 70 minutes. Data collection techniques in this study using tests, observations, and documentation. Data analysis technique consists of two stages. The first stage is the normality test and the second stage is the normality test and hypothesis test consisting of t test and test mastery learning. The result of the research shows that the use of communication experience-assisted model sharing model is effective on science learning outcomes of grade V students of SDN 1 Geneng District Jepon Blora regency for academic year 2016/2017. Keywords : experience sharing model, comic, science learning outcomes .